The Effect of Price Discount and Service Quality on Online Food Delivery Application on Student’s Purchase Decision at Universitas Negeri Yogyakarta - Abraheem Alsanousi Bilrras Ali, Yousef; Widayati, Ani (International Journal of Social Science, Education, Communication and Economics, 2025)
This study aims to understand how price sensitivity and limited purchasing power of students affect their purchasing decisions, and how service quality can play a role in increasing customer satisfaction and loyalty. This study is a quantitative study using a causal-comparative approach. This sampling is done using a purposive sampling technique. The researcher aims to collect data from 189 respondents with different backgrounds and characteristics. This research method uses IBM SPSS Statistics 26 software. The first hypothesis in this study is accepted because there is a positive influence between discounts on purchasing decisions. The second hypothesis can also be accepted because there is a positive influence between service quality on purchasing decisions. Price reductions in the form of discounts can increase the attractiveness of a product, make it more affordable, and motivate consumers to buy the product compared to products with normal prices. Quality service can increase customer satisfaction, which ultimately encourages consumers to make purchases. Consumers tend to prefer companies that provide a satisfying service experience because they feel appreciated and cared for. Good service quality will also increase consumer trust in the company, which is a key factor in making purchasing decisions. The limitations of this study were only conducted on students at Yogyakarta State University, so the results may not fully represent the general population of Grab Food users. Researchers examined discounts and service quality as independent variables. The data collected may only reflect conditions at a certain time. Respondents who are students may provide biased answers, especially if they feel that the questions in the questionnaire are too directed or less relevant.